Good Industrial Relations, Joint Problem Solving and HRM - Beaumont, Philip; Harris, Richard (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1996)
Do new human resource management practices fit comfortably with the existing collective bargaining relationship in unionized establishments? This is a question of concern to researchers in many advanced industrialized economies; this is particularly the case in Britain where human resource management practices are more a feature of the union, rather than nonunion, employment sector. The initial analysis of this paper, based on the 1990 national Workplace Industrial Relations Survey, indicates that an index of human resource management practices is negatively related to management reports of the quality of the existing employee-management relationship in unionized establishments, in contrast to the position in nonunion establishments. This finding is consistent with some existing case study research which indicates that human resource management practices are marginalizing the union-collective bargaining role in unionized organizations. However, a case study of the paper industry indicates that such marginalization does not occur if the existing relationship is more of a joint problem solving one.